Sistem Informasi Geografis Asrama Mahasiswa Aceh Berbasis LBS (Location Based Service) “Saweue Syedara” Berbasis Android - Alwie Augusra T. A; Kodrat Iman Satoto; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
Student Dormitory is a desirable place to live for all overseas Aceh students that far from home, Student Dormitory be exclusive if the existence of a dormitory is located very far from the government and from the student's hometown, so the presence of dormitory is felt not exist and far from elegant impression , there are many Aceh students dormitory are not recorded by the Regional Government , that recorded only dormitory under the auspices of the government, when in fact the most dormitory are located under other institutions. Along with the development of, make it even easier people's lives in their daily live. During its development, mobile technology can determine the position of users, find the location you want to target, and provide a route to that location. The use of mobile devices for the Aceh Government, Society, and students in particular is to facilitate them in the course of a visit to Student Dormitory. The geographic information system created using the Java programming language with SDK (Software Development Kit) Android and using MySQL and SQLite databases, the system is a client-server. The process of making and development of Geographic Information System using SDLC (Software Development Life Cycle) using prototyping life cycle. By using the life cycle of prototyping, the design can be quickly created and tested by users. Users can participate in helping the development of a system to provide feedback on the prototype that has been tried before, so that the system be made better. The result of this application design is the realization of a mobile application that can allow users to find information and search for Aceh Student Dormitory in Java Island, Indonesia. The Geographic Information System uses technology of LBS (Location Based Service), this allows users to find the location of dormitory that wish to visit. This system will be developed on mobile devices using the Android operating system.